Theoretical and experimental research of Carocell solar still - Tran, Xuan An; Hoang, Van Viet; Nguyen, The Bao (Journal of Technical Education Science, 2016)
The article describes the principle, specifications, theoretical basis and experimental results of Carocell solar still from Australia. The team has tested the Carocell Panell with the area of solar radiation absorbing surface of 2m2; the evaporator of 2m2; the internal condenser of 2m2 and the external condenser of 2m2; and the inlet water flow rate of 6 l/h. The results show that the water production of the still achieves 5kg/m2/day with an average radiation of 654 W/ m2 in Ho Chi Minh weather condition